Determinants of Teff (Eragrostis Tef) Market Outlet Choice in Woliso and Becho Districts of South West Shoa Zone Oromia Regional State, Ethiopia. - Deksiso, Hasen; Gebru, Getahun (Discoveries in Agriculture and Food Sciences, 2022)
This study was aimed to identifying determinants of (teff Eragrostis tef) the market outlet choice in Woliso and Becho districts of South West shoa zone. Both primary and secondary data were used in this study. Primary data was collected from 138 sampled farmers and 38 traders at different levels by using semi-structured interview. Descriptive analysis and econometric model multivariate probit model were employed to analyze the cross-sectional data. The output results suggest that households had three major market outlet choices (wholesalers, Retailers and other agents like (coop, union) and separate estimation of choice of the three outlets were biased since the choice decisions were interdependent and simultaneous. The joint probability of choosing all the three outlets was 0.63 percent and the probability of failure to the three outlets was only 6.1 percent. The results indicate that smallholder farmers choose at least two outlets at a time. The choice of producers on the three outlets was determined by similar underlying factors. District, Age, total family size, Education level, Farm size, Farming experience, off farm, Livestock (Tlu), Access to market information, Extension service, Access to credit and quantity produced. The outlet choice of Wholesalers was influenced by Education level, off- farm and quantity produced positively. Education level, Farming experience and off- farm were significant determinants of the retailors’ outlet choices negatively and age was positively influence. Other agent market outlet was also negatively and significantly affected by district, livestock ownership and off farm and family size is positively affect it. Therefore, efforts are needed to promote producers to choose wholesalers and retailers outlet since they enable them to get premium price margin. Strongly what should be given more emphasizing from government side is to strength union and cooperative organization available in area.